Tracking King Tiger : Reies Lopez Tijerina and the FBI - Gutiérrez, José Angel (Latinos in the United States series, 2019)
"This book explores the life of Reies Lopez Tijerina, with a particular focus on the FBI's treatment of him and his family"--